Effectiveness of acupuncture for irritable bowel syndrome: Protocol for a scoping review of systematic reviews and meta-analyses. Issue 29 (22nd July 2022) - Li, Yachen; Peng, Sike; Liang, Fangyuan; Liu, Suzhen; Li, Jia
Abstract : Background: Irritable bowel syndrome (IBS) is a common functional bowel disorder. Many systematic reviews/meta-analyses indicate that acupuncture and related therapies are effective for IBS. However, the robustness of the results in the systematic reviews and meta-analyses has not been evaluated. This scoping review aims to ascertain the credibility of current evidence of acupuncture therapy for IBS, to provide clinical research investigators with reliable information. Methods: Searches of China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), China Biology Medicine disc (CBMdisc), and Wanfang Database since the establishment of the database to February 2022. Study selection and data extraction will be conducted by 2 reviewers, and the quality will be assessed by 2 trained reviewers. We will use Assessment of Multiple Systematic Reviews-2 (AMSTAR2) for methodological quality assessment, Preferred Reporting Items for Systematic Reviews and Meta-Analyses for report quality assessment, Grading of Recommendations, Assessment, Development, and Evaluation for the quality of evidence assessment, and the Risk of Bias in Systematic Reviews for the bias assessment. Results: The results will be published in a peer-reviewed journal. Trial registration number: INPLASY202210117. Conclusion: This scoping review will provide comprehensive evidence of acupuncture for patients with irritable bowel syndrome. Ethics and dissemination: This scoping review does not require ethical approval as it is a secondary assessment of available literature.